PERSEPSI GURU TERHADAP GAYA SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - NABILA PUTRI AZAHRA Nabila; Jamilus (STKIP Subang, 2026)
This study aims to analyze teachers’ perceptions of the principal’s supervisory style in improving the quality of learning, motivated by the gap between the ideal concept of supervision and its implementation in practice, which is still often perceived as merely an administrative activity. This research employed a qualitative approach with a descriptive study design, using in-depth interviews, observations, and documentation as data collection techniques to obtain a comprehensive understanding of teachers’ experiences and perspectives. The findings reveal that teachers’ perceptions of supervision vary significantly and are influenced by supervisory style, communication quality, prior experiences, and the school work climate. Collaborative and reflective supervisory styles tend to receive positive responses because they encourage active participation and teachers’ professional development, whereas rigid directive styles may lead to resistance. In addition, effective communication through constructive and continuous feedback is considered a crucial factor in fostering positive teacher perceptions. The study also found that effective supervision should be contextual and adaptive to teachers’ characteristics and supported by a conducive work environment. Therefore, supervision should be positioned as a humanistic and participatory continuous guidance process in order to enhance teacher professionalism and optimize the quality of learning.